Amplifying Beneficiary Voices: A Qualitative Evaluation of the Family Hope Program (PKH) in Metro City via Most Significant Change - Mirnawati Mirnawati; Wahyu Widodo; Sigit Setioko (Utan Kayu Publishing, 2026)
The Family Hope Program (PKH), Indonesia's flagship Conditional Cash Transfer (CCT) initiative since 2007, has reached over 10 million Beneficiary Families (Keluarga Penerima Manfaat /KPM) nationwide. Despite its scale, evidence of program outcomes from the perspective of beneficiaries themselves remains limited. This study employs a qualitative descriptive approach using the Most Significant Change (MSC) technique to evaluate PKH achievements in Metro City, Lampung Province. Data were gathered through in-depth interviews, observations, and documentation with KPM participants and PKH Field facilitators s. Findings reveal that PKH has substantially improved access to education and health services, reduced household expenditure burdens, and fostered behavioral independence in accessing public services. Community resilience, particularly evident during the COVID-19 pandemic, and the sustained guidance of Field facilitators s emerged as pivotal factors in amplifying program outcomes. However, PKH's effectiveness in raising household income, reducing poverty and inequality, and introducing formal financial products remains limited and requires policy reinforcement. These findings provide evidence-based recommendations for strengthening PKH implementation and future social protection programs in Indonesia.